Synthesis, Characterization and Crystal Structure of Acetohydroxamate-Coordinated Molybdenum(VI) Complex Derived from 2-[(2-Ethylaminoethylimino)methyl]-4-methoxyphenol - Zhang, Wei-Ming; Qian, Shao-Song; You, Zhonglu (Asian Journal of Chemistry, 2014)
Reaction of [MoO2(acac)2] (where acac = acetylacetonate) with 2-[(2-ethylaminoethylimino)methyl]-4-methoxyphenol (L) and acetohydroxamic acid (H2AHA) in methanol yielded a new mononuclear molybdenum(VI) complex, [MoO2L(AHA)]. Crystal and molecular structure of the complex were determined by single crystal X-ray diffraction method. The complex was further characterized by IR and elemental analysis and thermogravimetric analysis. Single crystal X-ray structural studies indicate that the zwitterionic Schiff base ligand L coordinates to the MoO2 core through the phenolate oxygen and azomethine nitrogen and the dianionic AHA ligand coordinates to the MoO2 core through the two oxygen atoms. The Mo atom in the complex is in octahedral coordination. Crystal structure of the complex is stabilized by intermolecular N-H···N and C-H···O hydrogen bonds, as well as p···p interactions.